A1 and A2A adenosine receptors play a protective role to reduce prevalence of autoimmunity following tissue damage. (2nd June 2021) - Riff, Reut; Naamani, Oshri; Mazar, Julia; Haviv, Yosef S.; Chaimovitz, Cidio; Douvdevani, Amos
Summary: Adenosine is a potent modulator that has a tremendous effect on the immune system. Adenosine affects T cell activity, and is necessary in maintaining the T helper/regulatory T cell (Treg ) ratio. Adenosine signalling is also involved in activating neutrophils and the formation of neutrophil extracellular traps (NETs), which has been linked to autoimmune disorders. Therefore, adenosine, through its receptors, is extremely important in maintaining homeostasis and involved in the development of autoimmune diseases. In this study, we aim to evaluate the role of adenosine A1 and A2A receptors in involvement of autoimmune diseases. We studied adenosine regulation by NETosis in vitro, and used two murine models of autoimmune diseases: type I diabetes mellitus (T1DM) induced by low‐dose streptozotocin and pristane‐induced systemic lupus erythematosus (SLE). We have found that A1 R enhances and A2A R suppresses NETosis. In addition, in both models, A1 R‐knock‐out (KO) mice were predisposed to the development of autoimmunity. In the SLE model in wild‐type (WT) mice we observed a decline of A1 R mRNA levels 6 h after pristane injection that was parallel to lymphocyte reduction. Following pristane, 43% of A1 R‐KO mice suffered from lupus‐like disease while WT mice remained without any sign of disease at 36 weeks. In WT mice, at 10 days A2A R mRNA levels were significantly higher compared to A1R‐KO mice. Similar to SLE, in the T1DM model the presence of A1 R and A2A R was protective. Our data suggest that, in autoimmune diseases, the acute elimination of lymphocytes and reduction of DNA release due to NETosis depends upon A1 R desensitization and long‐term suppression of A2A R. Abstract : The role of adenosine A1 and A2A receptors in the development of autoimmune diseases. In both diabetes and lupus models, A1 R‐KO mice were predisposed to the development of autoimmunity. We also found that A1 R enhances and A2A R suppresses NETosis. Our data suggest that in autoimmune diseases, the acute elimination of lymphocytes and reduction of DNA release, due to NETosis, depends on A1 R desensitization and long‐term suppression of A2A R.